Fragmentation patterns of forest and cerrado vegetation in northeastern Mato Grosso - Maia Aveiro Cessa, Raphael; do Amaral, Uirá; Gimenes Rodrigues Silva, Felipe; Cometti, Nilton Nélio (Revista Agrogeoambiental, 2022)
This study sought to evaluate the fragmentation patterns of the forest and cerrado vegetation in the northeast of the state of Mato Grosso. The investigation used landscape metrics after extracting those fragments from the shapefile of soil use and occupation of the state of Mato Grosso and their application on the file of a negative buffer of 50.00. Forest and cerrado fragments were grouped into size classes in hectares. The quantified and specialized landscape metrics were area (mean perimeter/area ratio, core areas index, edge density), shape (mean shape indicator) and proximity (distance from the nearest neighbor in meters and the proximity index). The northeast of the state of Mato Grosso is occupied by 34.81% and 27.22% of the forest and cerrado fragments, respectively. The sum of the areas of the larger area size classes (classes >10,000 to 30,000 ha and >30,000 ha) is higher for forest fragments, which is indicative of the more expressive presence of the Amazon biome in that region and evidence of a more significant anthropic pressure on the fragmentation of the cerrado. In the northeast of the state of Mato Grosso, larger areas of forest and cerrado fragments are more protected than the smaller areas, as they have a smaller internal/external area ratio, higher percentage of central area, and less participatory border in relation to the total area.